IMPROVEMENT OF MATHEMATICAL PROBLEM SOLVING SKILL THROUGH THE POWER OF TWO LEARNING STRATEGIES AT GRADE VIII OF SMP N 1 ROKAN IV KOTO - septianingsih, rika; Eka Afri, Lusi (Universitas Pasir Pengaraian, 2016)
The aim of the research was to determine the improvement of mathematical problem solving skills through the power of two learning strategies at grade VIII of SMP N 1 Rokan IV Koto. Quasi Eksperimental research used Randomized Control Group Pretest-Posttest design. The population of the research was entire student grade VIII of SMP N 1 Rokan IV Koto.Random sampling technique used to selecting the sample. The power of two learning strategies used at the experimental class and traditional learning strategies used the control class. The instrument that used in this research was test. Before analysing the data, prequisite analysis was needed. The normality of data was calculated through Lilliefors. The result showed the data were not normaly distributed. Then, Mann Whitney was used to test. The hypotesis it was found zobserved = 3.586 and ztable = 2.24. It means zobserved> ztabel, H0 was rejected. It can be concluded that there was an improvement of mathematical problem solving skill through the power of two learning strategies at grade VIII of SMP N 1 Rokan IV Koto.